Percepciones sobre la gratitud en el voluntariado de una Organización No Gubernamental de Lima - Puig Otoya, Sebastian Agustin (2020)
Psychological Resilience is the ability to face adversity that distress the person, managing to maintain accurate functioning and even reach subsequent growth. The purpose of this paper is to deepen into the empirical evidence of the studies related to Psychological Resilience and Job Performance in professionals. The studies for this review were checked against the PRISMA criteria (Urrutia and Bonfill, 2010). The data searching through PsycNet, Redalyc, PubMed and Scopus- selecting papers focusing on the correlation of the variables presented. The papers selected for the analysis are related to the study of Psychological Resilience and its correlation to Job Performance (n =07). In general, this review set the basis for better understanding of the relationship between Psychological Resilience and Job Performance, finding that a higher level of Psychological Resilience an improve Job Performance presents, in adversity as well as in the context of positive stressful situations as well as promotion, new job responsibilities and a promotion.